The Aedes aegypti glutathione transferase family - Lumjuan, Nongkran; Stevenson, Bradley J.; Prapanthadara, La-aied; Somboon, Pradya; Brophy, Peter M.; Loftus, Brendan J.; Severson, David W.; Ranson, Hilary (Insect biochemistry and molecular biology, 2007)
In this report, we describe the glutathione transferase (GST) gene family in the dengue vector Aedes aegypti and suggest a novel role for a new class of mosquito GSTs. Twenty-six GST genes are present in Ae. aegypti, two of which are alternatively spliced to give a total of 29 transcripts for cytosolic GSTs. The six classes identified in other insect species are all represented and, as in Anopheles gambiae, the majority of the mosquito GSTs belong to the insect-specific Delta and Epsilon classes with eight members each. Sixteen secure 1:1 orthologs were identified between GSTs in Ae. aegypti and An. gambiae, but only four of these have recognisable orthologs in Drosophila melanogaster. Three mosquito-specific GSTs were identified which did not belong to any previously recognised GST classes. One of these, GSTx2, has been previously implicated in conferring 1,1,1-trichloro-2,2-bis-( p-chlorophenyl)ethane (DDT) resistance in Ae. aegypti from South America. However, we found no evidence for increased levels of this GST protein in DDT/pyrethroid-resistant populations from Thailand. Furthermore, we show that the recombinant GSTX2-2 protein is unable to metabolise DDT. Interestingly, GSTX2-2 showed an affinity for hematin, and this, together with the restricted distribution of this class to haematophagous insects, may indicate a role for these enzymes in protecting mosquitoes against heme toxicity during blood feeding.